2017
DOI: 10.1515/geosc-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of children’s travel to school, their body weight, spatial factors, and perceptions: A survey on nine European cities

Abstract: Abstract:Increasing rates of body weight of children has become a motivation for investigating active transportation to school during the past years. Lack of proper data covering different geographical contexts is a problem seen in the literature of this subject. The present paper reports the findings of a recent survey on nine cities in seven European countries funded by the European Commission. The objective of the survey was to provide data covering several topics in relation with active commuting to school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
6
0
2
Order By: Relevance
“…[14][15][16][17][18][19][20][21][22][23][24] Of these, 18 studies were included in evidence synthesis. [14][15][16][17][18][19][20][21][22][23][24]34,39,47,51,62,69,70,76,81,84,90,100 The stages of search and study selection process are summarized in Figure 1. From the additional internet searches, we selected examples of key national-and county-level physical activity policies, programs, and infrastructure (Supplementary Tables S4 and S5 [available online]).…”
Section: Search and Study Selection Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19][20][21][22][23][24] Of these, 18 studies were included in evidence synthesis. [14][15][16][17][18][19][20][21][22][23][24]34,39,47,51,62,69,70,76,81,84,90,100 The stages of search and study selection process are summarized in Figure 1. From the additional internet searches, we selected examples of key national-and county-level physical activity policies, programs, and infrastructure (Supplementary Tables S4 and S5 [available online]).…”
Section: Search and Study Selection Resultsmentioning
confidence: 99%
“…In a study conducted among 211 parents of primary school students in Rijeka, 54.1% of participants were satisfied with the quality of sidewalks, but only 13.2% were satisfied with the quality of bike paths. 62 In the same study, 41.7% of parents perceived their child's routes to school, including sidewalks and bike lanes, safe for active commuting, while 54.5% of them reported that their children perceive the routes to school safe for active commuting. 62 Taking into account that: (1) all Croatian counties have policies/programs and infrastructure for the promotion of sports and physical activity, and (2) that most aspects of community and environmental support to physical activity were perceived positively by 40.0% to 60.0% of parents and children, the expert panel assigned the grade B− to this indicator.…”
Section: Community and Environmentmentioning
confidence: 92%
“…Circunstancias socioeconómicas, ambientales y la percepción de los padres y madres de los escolares podrían explicar los resultados hallados en la presente investigación. Son varios los autores que encuentran relaciones significativas entre el desplazamiento activo y las percepciones de los padres y madres, concluyendo que los escolares se transportan de forma menos activa cuando existe la preocupación por características del entorno como el exceso de tráfico, la adaptabilidad del recorrido para el peatón o ciclista, el alumbrado, las aceras o el entorno socioeconómico del barrio (Aarts, Mathijssen, van Oers, & Schuit, 2013;Huertas-Delgado et al, 2017;Kerr et al, 2006;Masoumi et al, 2017;Molina-García & Queralt, 2017;Oluyomi et al, 2014;Panter, Jones, van Sluijs, & Griffin, 2010;Timperio et al, 2006). Otro aspecto a considerar es la distancia y la pendiente del recorrido, ya que las rutas menores a 800 metros o con poca inclinación se asocian con un mayor desplazamiento activo (Timperio et al, 2006).…”
Section: Discussionunclassified
“…However, those students who travel longer distances accrue more significant amounts of PA and health benefits [82]. The physical environment in which students live impacts their travel patterns [83,84]. Community density, diversity, and design have consistently been linked with personal travel behavior and are considered the most influential built environment factors in active travel [85].…”
Section: Active Transportmentioning
confidence: 99%